Respiratory failure and death in vulnerable premature children with lower respiratory tract illness - Ofman, Gaston (2020)
Background. Efforts to better understand the risk factors associated with respiratory failure (RF) and fatal lower respiratory tract infection (LRTI) in premature children in developing countries are necessary to elaborate evidenced-based preventive interventions. We aim to characterize the burden of respiratory syncytial virus (RSV) and human metapneumovirus (hMPV) LRTI in premature children and determine risk factors for RF and fatal illness in a vulnerable population. Methods. This is a prospective, population-based, cross-sectional study. Subjects with severe LRTI were enrolled during respiratory season. Risk factors for RF and death in premature infants were investigated. Results. A total of 664 premature children participated. Infant's hospitalization rate due to LRTI was 82.6/1000 (95% confidence interval [CI], 68.6-96.7/1000). Infant's RSV and hMPV rates were 40.9/1000 (95% CI, 36.3-45.6/1000) and 6.6/1000 (95% CI, 3.9- 9.2/1000), respectively. The RF rate was 8.2/1000 (95% CI, 4.9-11.5/1000). The LRTI mortality was 2.2/1000 (95% CI, 0.7-3.7/1000); for RSV, the rate was 0.8/1000 (95% CI, 0-1.7/1000) with a case-fatality ratio of 1.8%. Never breastfeeding, malnutrition, younger than 6 months, congenital heart disease, and lower hematocrit were risk factors for RF. Experiencing pneumonia, pneumothorax, sepsis, or apnea were clinical determinants of poor outcomes. Conclusions. Premature children under 2 years old in vulnerable environments experience RF and death more often than term counterparts. Modifiable risk factors associated with poor outcomes should prompt evidence-based interventions.